Freelancing, translating, observing: Association4U case study - Paliichuk Elina (SHS Web of Conferences, 2021)
The paper presents an overview of the freelance practice in the Ukrainian translation industry through the lens of the role of Associate Translation Fellow at “Association4U” EU-funded technical aid project (Phase I) aimed at supporting approximation of Ukrainian laws to EU legislation. To meet the challenges of the ever-changing political world, translators should be able to build specific capacities. Under the microscope of the observations made is the range of competences which a contemporary translator should have to maintain a competitive profile in institutional translation domain. An institutional translator’s portrait has been drawn up based on the A4U case, which became possible due to feedbacks given to junior fellows and stylistic analysis of the translated texts. The studies of acquis communautaire provide insights into the stylistic peculiarities of translation of the EU acts in the context of the Ukrainian language. Key attention is given to cognitive, stylistic, and discursive aspects of translation process. The paper deals with a complex of the general philological background and specific skills of translation experts, which is a pre-requisite of accurate translation in the framework of academic, industrial, and institutional realms.